2017
DOI: 10.1002/2017ja023909
|View full text |Cite
|
Sign up to set email alerts
|

A mechanism of midlatitude noontime foE long‐term variations inferred from European observations

Abstract: Manually scaled June noontime monthly median foE values at three European stations Rome, Juliusruh, and Slough/Chilton were used to understand the mechanism of foE long‐term variations. The 11 year running mean smoothed foE manifests long‐term (for some solar cycles) variations with the rising phase at the end of 1960–1985 and the falling phase after 1985. A close relationship (even in details) between (foEave)11y and (R12)11y variations with the correlation coefficient of 0.996 (absolutely significant accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…If our earlier assumptions, namely, using MSIS‐86 T 120 and S values, were wrong, we hardly could obtain good testing results in a comparison with CHAMP/STAR neutral gas density observations (Mikhailov & Perrone, ; Perrone et al, ). Also, a good coincidence of the retrieved EUV with the EUVAC model by Richards et al () was also shown by Mikhailov et al () and by Mikhailov and Perrone (). It should be stressed that the EUVAC model has nothing common with our method; that is, this is an absolutely independent check of the method.…”
Section: Methods Descriptionsupporting
confidence: 69%
“…If our earlier assumptions, namely, using MSIS‐86 T 120 and S values, were wrong, we hardly could obtain good testing results in a comparison with CHAMP/STAR neutral gas density observations (Mikhailov & Perrone, ; Perrone et al, ). Also, a good coincidence of the retrieved EUV with the EUVAC model by Richards et al () was also shown by Mikhailov et al () and by Mikhailov and Perrone (). It should be stressed that the EUVAC model has nothing common with our method; that is, this is an absolutely independent check of the method.…”
Section: Methods Descriptionsupporting
confidence: 69%
“…We have not also discussed the retrieved solar EUV fluxes. On one hand, we have already presented and discussed our results on EUV earlier (Mikhailov et al, 2017;; on the other hand, this topic should be considered in relation with any geophysical problem, while this paper is devoted to the method and its testing using reliable CHAMP/STAR neutral gas density observations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies by Perrone and Mikhailov (; hereafter designated PM17) and Mikhailov et al () used a single ionospheric measurement parameter, foF1, to derive a set of four neutral atmospheric parameters (exospheric temperature T e x , neutral concentrations [O], [O 2 ], and [N 2 ]) and one solar EUV flux factor ( f ). They used these results to analyze long‐term trends in the thermosphere and ionosphere.…”
Section: The Methods Using a Single Ionospheric Parameter Fof1 For Calmentioning
confidence: 99%
“…In particular, PM17 studied T e x over multiple solar cycles and compared them to existing temperature trends from multiple observation sets using ISRs. The study states that “routine ISR observations based on a fixed model of ion composition may be not appropriate for long‐term trend analyses.” These authors have also published separate studies (Mikhailov & Perrone, , ; Mikhailov et al, ) examining long‐term trends in the ionosphere and thermosphere using results from the same derivation technique. We assert in this commentary that several aspects of the technique as described introduce large analysis difficulties and that the resulting ambiguities in derived parameters make them unsuitable for precise quantitative ionospheric and thermospheric long‐term trend studies.…”
Section: The Methods Using a Single Ionospheric Parameter Fof1 For Calmentioning
confidence: 99%
See 1 more Smart Citation